2004
DOI: 10.1093/hmg/ddh050
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the first mannosylation step in the N-glycosylation pathway causes congenital disorder of glycosylation type Ik

Abstract: Defects of N-linked glycosylation represent diseases with multiple organ involvements that are classified as congenital disorders of glycosylation (CDG). In recent years, several CDG types have been attributed to defects of dolichol-linked oligosaccharide assembly in the endoplasmic reticulum. The profiling of [3H]mannose-labeled lipid-linked oligosaccharides was instrumental in identifying most of these glycosylation disorders. However, this method is poorly suited for the identification of short lipid-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 41 publications
0
61
0
1
Order By: Relevance
“…To separate 2AB-labeled oligosaccharides, we have adapted the procedure of Royle et al (Royle et al, 2002) using a three buffer solvent system (Grubenmann et al, 2004). We use a GlykoSep-N column maintained at 30 °C.…”
Section: Hplc Analysis Of 2ab-labeled Oligosaccharidesmentioning
confidence: 99%
“…To separate 2AB-labeled oligosaccharides, we have adapted the procedure of Royle et al (Royle et al, 2002) using a three buffer solvent system (Grubenmann et al, 2004). We use a GlykoSep-N column maintained at 30 °C.…”
Section: Hplc Analysis Of 2ab-labeled Oligosaccharidesmentioning
confidence: 99%
“…In this case, based on a phenotypic analysis of a mutant in a yeast CDG homolog (Imbach et al, 1999) and its rescue by the human homolog, a screen was devised to identify other genes acting in the same glycosylation pathway in yeast. Subsequently, it was found that mutations in human homologs of these newly identified yeast genes caused CDG (Westphal et al, 2002;Imbach et al, 2000;Grubenmann et al, 2004). Thus, model genetic systems can be viewed as first pass in vivo filters or as bgenetic bioassaysQ to search for relevant genetic interactions among a potentially large set of genes.…”
Section: The Role Of Model Systems In Identifying Loci Contributing Tmentioning
confidence: 99%
“…Furthermore, on the basis of in silico analysis, some CDG patients would be expected to carry loss of O-or N-glycosylation mutations in the corresponding glycosylation enzyme (G Vogt et al, unpublished). For example, a loss of N-glycosylation has been reported for one mutant enzyme involved in O-glycosylation [12]; nine examples have been reported in which a loss of O-glycosylation was observed in two mutant enzymes involved in N-glycosylation [13,14] and in seven mutant enzymes involved in O-glycosylation [15][16][17][18]. Intriguingly, pathogenic mutations involving gains of glycosylation also occur and, paradoxically, some of these mutations also affect glycosylation enzymes and cause CDGs (see below).…”
Section: Introductionmentioning
confidence: 99%